2017
DOI: 10.1093/ofid/ofx033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Mucosal Immune Correlates of HIV-1 Semen Levels in Antiretroviral-Naive Men

Abstract: Background.This study was done to characterize parameters associated with semen human immunodeficiency virus (HIV)-1 ribonucleic acid (RNA) viral load (VL) variability in HIV-infected, therapy-naive men.Methods.Paired blood and semen samples were collected from 30 HIV-infected, therapy-naive men who have sex with men, and 13 participants were observed longitudinally for up to 1 year. Human immunodeficiency virus RNA, bacterial load by 16S RNA, herpesvirus (Epstein-Barr virus and cytomegalovirus [CMV]) shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Because viral load in semen has been correlated in several studies to the seminal concentrations of various inflammatory cytokines ( 17 21 ), we also tested whether inflammation levels in male genital organs could influence tissue viral load and shedding in semen. Using mRNAs of 6 cytokines, which are known to correlate with HIV semen levels (tumor necrosis factor alpha [TNF-α], interleukin 1β [IL-1β], gamma interferon [IFN-γ], CCL2, and IL-10) ( 18 , 19 , 21 , 22 ) or are elevated in HIV-infected patients (IL-8) ( 20 , 23 , 24 ), we measured inflammation levels within all the male genital organs, excluding the urethra due to limited material ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because viral load in semen has been correlated in several studies to the seminal concentrations of various inflammatory cytokines ( 17 21 ), we also tested whether inflammation levels in male genital organs could influence tissue viral load and shedding in semen. Using mRNAs of 6 cytokines, which are known to correlate with HIV semen levels (tumor necrosis factor alpha [TNF-α], interleukin 1β [IL-1β], gamma interferon [IFN-γ], CCL2, and IL-10) ( 18 , 19 , 21 , 22 ) or are elevated in HIV-infected patients (IL-8) ( 20 , 23 , 24 ), we measured inflammation levels within all the male genital organs, excluding the urethra due to limited material ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we first examined the infection level and inflammation status of all of the 4 organs (testis, epididymis, seminal vesicles, and prostate) involved in semen elaboration, as well as of 2 ducts involved in semen transport (vas deferens and urethra) from 8 chronically infected macaques. Numerous studies reported a significant correlation between HIV shedding and elevated cytokine concentrations in semen, along with specific pattern of cytokine network in semen compared with blood, suggesting that inflammation favors the burst/release of virus from local sources ( 17 21 , 25 30 ). Our data showed no correlation between semen viral load and expression levels of proinflammatory cytokines such as TNF-α and IL-1β in infected semen-producing organs, preventing initial discrimination of potential tissue sources.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 infection is associated with dysregulation of seminal cytokines (38,39) as well as an increased semen/blood cytokine ratio (10,38,39). This proinflammatory environment has been suggested to increase viral replication, as semen viral load often correlates with cytokine levels (40), as well as the fact that several cytokines, including TNF-␣, directly act on the virus to increase replication (41) (reviewed in reference 42). A similar phenomenon is observed in men with classical STI such as gonorrhea or trichomoniasis (20).…”
Section: Discussionmentioning
confidence: 99%
“…HIV load in semen is usually lower than in blood, but patients with an exceptionally high semen viral load were reported (533,671,741). Factors associated with HIV shedding prevalence in semen are blood viral load (104,176,267,313,329), STIs (329,548), seminal CMV or EBV (226,227,229,394,482,523,628) and seminal cytokine levels (394,395,523,548); the two latter reflecting elevated inflammation, which enhances HIV replication.…”
Section: Prevalence and Pattern Of Virus Shedding In Semenmentioning
confidence: 99%